2020
DOI: 10.2105/ajph.2020.305812
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Prevention and Treatment: Misinformation on Pinterest, 2018

Abstract: Objectives. To quantify and describe the incidence of misinformation about breast cancer on the social media platform Pinterest, a leading source of women’s health (e.g., breast cancer) information. Methods. We performed a hand-coded content analysis on 797 Pinterest posts (“pins”) mentioning the terms “breast cancer” or “breast” and “cancer,” collected in November 2018. Results. From the original sample of 797, 178 (22.3%) made a factual claim about what social media users could do to prevent or treat breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…However, there is also a plethora of misinformation on internet sites-and on social media sites in particular. 139,140 Survivors report difficulty accessing credible nutrition information online 138 and may be especially vulnerable to claims that specific behavior changes can cure their cancer or extend survival. One study of cancer-related nutrition and meal planning content in Pinterest 141 found that a substantial proportion claimed a particular food or recipe prevented, treated, or cured cancer.…”
Section: Community Influences On Survivor Nutrition and Physical Acti...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is also a plethora of misinformation on internet sites-and on social media sites in particular. 139,140 Survivors report difficulty accessing credible nutrition information online 138 and may be especially vulnerable to claims that specific behavior changes can cure their cancer or extend survival. One study of cancer-related nutrition and meal planning content in Pinterest 141 found that a substantial proportion claimed a particular food or recipe prevented, treated, or cured cancer.…”
Section: Community Influences On Survivor Nutrition and Physical Acti...mentioning
confidence: 99%
“…Evidence‐based information on nutrition and physical activity for cancer survivors is available online through sources such as the ACS, ACSM, and AICR. However, there is also a plethora of misinformation on internet sites—and on social media sites in particular 139,140 . Survivors report difficulty accessing credible nutrition information online 138 and may be especially vulnerable to claims that specific behavior changes can cure their cancer or extend survival.…”
Section: Community Influences On Survivor Nutrition and Physical Acti...mentioning
confidence: 99%
“…Nutrition research is subject to misinterpretation, distortion, and extrapolation, and much online cancer‐related misinformation pertains to food and supplements 1,6 . Most nutrition misinformation is a manifestation of “food faddism,” the exaggerated belief that certain foods or food components can cure or cause disease or have special health benefits 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…We designed this study to explore the scope and features of cancer‐related nutrition information on a social media site, Pinterest. Pinterest is a media platform that is particularly friendly to nutrition and recipe content given its structure, visual nature, and ability to save content for later viewing 1,22‐25 . Here, we describe a content analysis intended to classify the types of cancer nutrition claims on Pinterest that stemmed from searching for cancer recipes as well as the features of this content that were used to legitimize claims.…”
Section: Introductionmentioning
confidence: 99%
“…It can influence people's decisions that negatively impact their emotions, healthcare choices, positive life attitudes, and personal well-beings [45,46]. For example, if cancer patients were provided misinformation about their cancer treatment choices, misinformation could be negatively impacting their good path of treatment and sometime this kind of misinformation could be fatal [55].…”
Section: Introductionmentioning
confidence: 99%